Deregulation of linc-PINT in acute lymphoblastic leukemia is implicated in abnormal proliferation of leukemic cells - Garitano-Trojaola, Andoni (Oncotarget, 2018)
Long Non-Coding RNAs (lncRNAs) are functional RNAs longer than 200 nucleotides in length. Several lncRNAs are involved in cell proliferation and are deregulated in several human tumors. Few lncRNAs have been described to play a role in Acute Lymphoblastic Leukemia (ALL). In this study, we carried out a genome wide lncRNA expression profiling in ALL samples and peripheral blood samples obtained from healthy donors. We detected 43 lncRNAs that were aberrantly expressed in ALL. Interestingly, among them, linc-PINT showed a significant downregulation in T and B-ALL. Re-expression of linc-PINT in ALL cells induced inhibition of leukemic cell growth that was associated with apoptosis induction and cell cycle arrest in G(2)/M phase. linc-PINT induced the transcription of HMOX1 which reduced the viability of ALL cells. Intriguingly, we observed that treatment with anti-tumoral epigenetic drugs like LBH-589 (Panobinostat) and Curcumin induced the expression of linc-PINT and HMOX1 in ALL. These results indicate that the downregulation of linc-PINT plays a relevant role in the pathogenesis of ALL, and linc-PINT re-expression may be one of the mechanisms exerted by epigenetic drugs to reduce cell proliferation in ALL.